Analisis Pemanfaatan Alam Sekitar Dalam Pembelajaran IPA Di Madrasah Ibtidaiyah - Nurhalizah Liza; Zaini Dahlan (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2022)
Science learning is an important lesson for students so that they can take advantage of their natural surroundings properly and correctly. This research was conducted because teachers rarely use the natural surroundings as a source or media in their learning, especially on science material, even though using the natural environment in science learning can make children pay more attention to the natural surroundings. The purpose of this study is to analyze the use of the natural surroundings in the teaching and learning process of science at the Nurul Iman Private Madrasah, Limau Manis Village, Tanjung Morawa District, Deli Serdang Regency, North Sumatra. The author uses qualitative research methods and data collection techniques used in this study in the form of interviews and observations. The research subjects were science teachers in grades 1 to 6 and there were 6 teachers in the school. The survey results show that the use of the environment as a learning resource for science learning in schools makes learning activities more interesting and less boring for students. By utilizing the natural surroundings, it will be more meaningful and valuable, because these students will face real events and situations, students also benefit from the delivery of learning, and new media for students who are familiar with daily activities, and students can feel active in the learning process. Therefore, with the benefits that have been described, teachers should use nature in teaching science to elementary students to use nature as a learning resource.